In-situ preparation of novel sedimentary rock-like Fe3O4 by rice-husk mesoporous silica as templates for effective remove As(III) from aqueous solutions. Issue 5 (October 2021) - Hou, Jingjie; Weng, Ruoyi; Jiang, Weiwei; Sun, Huimin; Xia, Juntao; Liu, Yiting; Sheng, Jie; Song, Yishan
Abstract: Novel sedimentary rock-like Fe3 O4 (SR-Fe3 O4 ) was fabricated by a facile method using mesoporous silica derived from rice husk (RH-MCM-41) as a template and in-situ removing templates. SR-Fe3 O4 has been researched by various characterization technologies and used to remediate As(Ⅲ) from aqueous solutions. The influence of adsorption kinetics, isotherms and adsorption conditions on As(Ⅲ) removal were researched. Kinetic studies elucidated that the As(Ⅲ) adsorption onto SR-Fe3 O4 was best fitted by the pseudo-second-order model. The isotherms were best simulated by Sips model, and the maximum As(Ⅲ) adsorption capacity by SR-Fe3 O4 was 1002.03 mg/g under optimum condition, which was superior to the reported adsorbents. Thermodynamic results exhibited that the process of removing As(Ⅲ) was spontaneous and endothermic. The high sorption capacity existed in a wide pH range and As(III) removal was independent on pH values indicating electrostatic attraction was not the dominant removal mechanism. The concrete adsorption mechanism of As(III) was demonstrated by Fe–O–As complexes and hydrogen bond characterized by XPS and FTIR spectra. This unique structure provided highly exposed Fe–O bonding and hydrogen-bonding which enhanced the As(III) adsorption capacity. All these results evaluated that the synthesized SR-Fe3 O4 possessed great potentiality for As(III)-containing wastewater sequestration. Graphical Abstract: ga1 Highlights: ● Novel sedimentary rock-like Fe3 O4 was fabricated by a facile one-step coprecipitation method. ● The maximum As(Ⅲ) adsorption capacity of SR-Fe3 O4 derived from Sips equation was 1002.03 mg/g. ● The adsorption capacity of As(Ⅲ) maintained a high performance in a wide pH range of 3.0–10.0.